Sosialisasi dan Edukasi Pencegahan Penyebaran Covid-19 di Kalangan Ojek Online Jl. Adhiyaksa Kelurahan Masale Kota Makassar - Rahman, Qarnila Ridhaniah; Andu, Cristine Purnamasari; Litta, Lista; Budiawan, Budiawan; Dengen, Alvianus (Universitas Patria Artha, 2021)
Pandemic Corona Virus Diseas 2019 (Covid-19). Covid-19 is not the first virus to hit Indonesia because there have been other viruses such as the dengue fever virus and the bird flu virus which spread quite massively. The theme that is the focus of this program is socialization and education on preventing the transmission of COVID-19 by emphasizing Clean and Healthy Living Behavior. The method used in this program is socialization to online motorcycle taxis on Jalan Adiyaksa in Masale Village, Makassar City. This program consists of several activities such as distribution of amphlets and distribution of brochures, socialization of healthy living, Clean and Healthy Living Behavior, hand washing training, physical distancing habits, providing masks, and providing hand sanitizer assistance. The evaluation is carried out by considering the benefits of the program, the accuracy of the target and the accuracy of the method. This activity can help online motorcycle taxis find information about Covid-19 and be able to provide provisions for preventing the transmission of Covid-19 by implementing a clean and healthy lifestyle. In addition, by providing an understanding of health protocols which include Clean and Healthy Living Behavior, routine hand washing and physical distancing habits, in daily life, it is hoped that the spread of Covid-19 in Indonesian society in general and the people of Lombok in particular can be stopped immediately.Keywords: Online Ojek, Covid-19, Education